Pengaruh Remote Working Terhadap Employee Engagement Pada Karyawan Generasi Z (Studi Kasus Pada Perusahaan Startup di Kota Bandung) - Vania Citta Mufarrihati; R. Rina Novianty Ariawaty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Generation Z has now entered a work environment that was previously only filled with Generation X and Millennials. With Generation Z's preference for remote working, companies need to prepare and adapt to this phenomenon. However, remote working apparently has advantages and disadvantages that can increase or decrease the level of employee engagement in the company. Especially in startup companies, which started to become popular during the COVID-19 pandemic, most of them implemented remote working. Apart from that, as many as 49.5% of startup employees are from generation Z, so it needs to be a priority so that companies have a high level of employee engagement. Due to the fact that only 10% of startups in Indonesia can survive and 26% fail due to low levels of employee engagement. This research aims to determine the relationship between remote working and employee engagement among generation Z employees of startup companies in the city of Bandung. Sample in this research was 120 people from the generation Z who currently/have (at least 3 months) worked at a startup company in Bandung city. By determining the sample using purposive sampling with the hair’s formula. The method used in this research uses descriptive and verification methods with a quantitative approach, which is measured using a simple linear regression test. The results of this research show that remote working has a positive influence on employee engagement.